Resistance Training, Lipid Profile, and Homocysteine in Patients with Alzheimer's Disease - Vital, Thays Martins [UNESP]; Soleman Hernandez, Salma S. [UNESP]; Stein, Angelica Miki [UNESP]; Garuffi, Marcelo [UNESP]; Ligo Teixeira, Camila Vieira [UNESP]; Santos-Galduroz, Ruth Ferreira [UNESP]; Riani Costa, Jose Luiz [UNESP]; Stella, Florindo [UNESP] (Elsevier B.V., 2016)
Background: The aims of this study were to verify the relation of the level of physical activity with the lipid profile and the homocysteine and to investigate the effects of resistance training on the concentrations of metabolic variables of patients with Alzheimer's disease. Methods: Initially, the sample consisted of 37 community-dwelling patients with Alzheimer's disease. Eventually, only 30 patients participated in the intervention protocols offered, and they were divided into two groups: a training group with 14 patients and a social interaction group with 16 patients. All patients were evaluated using several instruments. We also analyzed the levels of serum homocysteine and lipid profiles. Results: There were no significant relations between level of physical activity, lipid profile, and homocysteine. The training group exhibited reduced total cholesterol and low-density lipoprotein (LDL), as well as increased concentrations of high-density lipoprotein (HDL). However, the social interaction group exhibited decreased total, LDL, and HDL cholesterol. There were no significant differences in the homocysteine concentrations for the two groups. Conclusion: No relationships were found between physical activity and metabolic variables. For both groups, changes were observed in the concentrations of total, LDL, and HDL cholesterol. Copyright (C) 2016, Taiwan Society of Geriatric Emergency & Critical Care Medicine. Published by Elsevier Taiwan LLC.
Keywords: cholesterol; dementia; exercise; homocysteine; physical activity